Pengaruh Sektor Tersier terhadap Pertumbuhan Ekonomi Kawasan Barat dan Timur Indonesia - Pramudya Kusuma; Aisyah Fitri Yuniasih (Politeknik Statistika STIS, 2021)
The tertiary sector is a sector that produces products in the form of services. The tertiary sector itself dominates the economy in Indonesia. Changes in the economic structure towards the tertiary sector are expected to affect economic growth, so this study was conducted to analyze the effect of the tertiary sector on the economic growth of the provinces in Indonesia. The analysis carried out divides the provinces in Indonesia into the Western Region of Indonesia (KBI) and the Eastern Region of Indonesia (KTI). The method used is Fixed Effects Model panel data analysis with Feasible Generalized Least Squares estimation. The results showed that in KBI and KTI, the tertiary sector which was explained by labor productivity and labor share had a positive effect on economic growth. Another variable used is direct government spending which has a positive effect on economic growth and the rate of population growth has a negative effect on economic growth. Increasing the productivity of the tertiary sector and the share of labor in the tertiary sector can be carried out as an effort to increase economic growth.